Plasma concentrations after oral or intramuscular vitamin K1 in neonates. Issue 9 (September 1985) - McNinch, A W; Upton, C; Samuels, M; Shearer, M J; McCarthy, P; Tripp, J H; L'E Orme, R
Abstract : One hundred and seven healthy, breast fed infants received 1 mg vitamin K1 either at birth (orally or intramuscularly) or with the first feed (orally). Venous blood samples collected in the next 24 hours were assayed for plasma vitamin K1. In babies given the vitamin orally at birth, the peak median concentration (73 ng/ml) occurred at four hours. By 24 hours median plasma concentrations had fallen to 23 ng/ml and 35 ng/ml in the groups fed vitamin K1 at birth or with the first feed, respectively; this difference was not, however, significant. Plasma concentrations after intramuscular injection exceeded those in the oral groups at all comparable times, with a peak median concentration of 1781 ng/ml at 12 hours falling to 444 ng/ml at 24 hours. Since median plasma vitamin K1 concentrations 24 hours after oral administration were some 100 times and 1000 times greater than previously estimated adult and newborn values respectively, this study supports giving vitamin K1 orally at birth to well, mature babies to protect against early haemorrhagic disease of the newborn. Further studies are needed to determine the optimum dose for protection over subsequent weeks.